The Influence of Additional Food Hotong Porridge with Moringa Leaves Mixture on Improvement Nutritional Status of Children Nutritional Children (Medico Legal Update, 2020)
Malnutrition is one of the main nutritional problems in Indonesia. Toddler is one of the age groups that are vulnerable to nutritional problems. One of the causes immediate nutritional problem is a lack of energy. This study aims to analyze the effect of supplementary feeding (PMT) hotong porridge mixed with moringa leaves and government biscuits on weight gain and underweight nutritional status in the working area of the Five Public Health Center. This study used Randomized Controlled Trial Design, with a quasi-experimental approach. The distribution of PMT hotong porridge with Moringa leaf mixture as a treatment group and the administration of PMT biscuits by the government program as a control group. The sample size was 32 toddlers. Data were analyzed using paired-sample T test. There was a significant effect on body weight and nutritional status after administration of PMT hotong porridge with moringa leaf mixture and PMT biscuits of government programs with p-value of 0.001 in the treatment group and the control group. Hotong slurry feeding and biscuit mix Moringa leaves government programs throughout a period of 30 days to take effect on the increase in body weight and nutritional status of children on the mark with most of the value of z-score infants already stood at -2SD s/d +2SD, which means that most of the children under five are already in the nutritional status of the mall.